2019
DOI: 10.1192/bjb.2019.69
|View full text |Cite
|
Sign up to set email alerts
|

Personal resilience for psychiatrists: systematic review

Abstract: Personal resilience for psychiatrists: systematic review I read with interest this article 1 which explores the factors that promote and maintain psychiatrists' well-being, particularly personal, workplace and non-work-related factors such as increased self-awareness, extending job roles, discrete work activities, and/or support from family or social environment. John. D. Yoon and Brendan M. Daley, studying the association between a sense of calling and physician well-being, 2 reported that a higher sense of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Several reviews on resilience among health care professionals have been undertaken in the current literature, but most of the reviews explored resilience‐promoting factors in physicians (Howard et al, 2019; McKinley et al, 2019; Senthil, 2019), nurses (Cusack et al, 2016; Powell et al, 2020; Yu et al, 2019), social workers (Truter et al, 2017) and health care professionals as a whole (Huey & Palaganas, 2020; Robertson et al, 2016; Zanatta et al, 2020). However, these reviews were limited in solely narrative analysis (Howard et al, 2019; McKinley et al, 2019; Zanatta et al, 2020) and few selected articles (Zanatta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews on resilience among health care professionals have been undertaken in the current literature, but most of the reviews explored resilience‐promoting factors in physicians (Howard et al, 2019; McKinley et al, 2019; Senthil, 2019), nurses (Cusack et al, 2016; Powell et al, 2020; Yu et al, 2019), social workers (Truter et al, 2017) and health care professionals as a whole (Huey & Palaganas, 2020; Robertson et al, 2016; Zanatta et al, 2020). However, these reviews were limited in solely narrative analysis (Howard et al, 2019; McKinley et al, 2019; Zanatta et al, 2020) and few selected articles (Zanatta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Burnout is characterized by three domains-exhaustion, increased negativism or emotional detachment in relation to one's job, and reduced professional efficacy [4]. It has been shown that psychiatrists tend to suffer from higher levels of psychological distress and burnout relative to other physicians, with female and junior psychiatrists among the most vulnerable [5,6]. Increased rates of burnout have been linked with compassion fatigue, vicarious traumatization, and negative transference [7]-factors highly relevant in the day-to-day work of a trainee psychiatrist.…”
mentioning
confidence: 99%